Characterization of compliant polymer concretes for rapid repair of runways. (1st March 2015) - Roh, In-Taek; Jung, Kyung-Chae; Chang, Seung-Hwan; Cho, Yoon-Ho
Highlights: Rubber-containing compliant polymer concretes were introduced for repairing runways. Tire waste powder enhances mechanical performance with high ductility factor. Best mixing ratio of compliant polymer concrete for repairing runways was determined. Abstract: A new type of compliant polymer concrete for runway repair is introduced in this paper. To enhance the compliance of epoxy-based polymer concrete, some epoxy resin was replaced with liquid-type silicone rubber or tire waste powder. To estimate the temperature dependency of the mechanical behavior of the compliant polymer concretes, mechanical tests were also carried out. It was found that tire waste powder was more efficient than the silicone rubber in terms of mechanical performance. The experimental work revealed the 72:20:08(T) specimen provided the highest ductility factor while keeping the compressive strength above the minimum required value (30 MPa).